On-surface photo-dissociation of C–Br bonds: towards room temperature Ullmann coupling1. Issue 63 (14th August 2015) - Basagni, Andrea; Ferrighi, Lara; Cattelan, Mattia; Nicolas, Louis; Handrup, Karsten; Vaghi, Luca; Papagni, Antonio; Sedona, Francesco; Valentin, Cristiana Di; Agnoli, Stefano; Sambi, Mauro
<x xml:space="preserve">Abstract</x> The surface-assisted synthesis of gold-organometallic hybrids on the Au(111) surface both by thermo- and light-initiated dehalogenation of bromo-substituted tetracene is reported.